Rekonstruksi Metodologi Keilmuan Syarah Hadis Klasik - Yunita Kurniati (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
This paper aims to review the methodology of classical hadith syariah. For this reason, the question of how the classical methodology of hadith is being pursued in this paper. The method used is qualitative with a literature study approach. The results obtained are that the Islamic scientific tradition began at the time of the Prophet (PBUH), in writing, then after entering into the time of friends then the Islamic scientific tradition was held in written form. It is also the beginning of the emergence of the tradition of hadith. Hadith shari'ah in oral form occurred during the time of the Prophet PBUH, while shari'ah hadith in written form occurred during the time of companions. The difference in scientific traditions, since the time of the Prophet, until friends also influence the use of the methodology of the tradition of tradition, even along with the development of the era of science and also the methodology in the tradition of tradition. The method used by hadith scholars in giving tradition is ijmali, which is a method that explains the meaning in general and concise. Even so a review of him in the present is very well done, especially for the development of scientific knowledge related to the tradition.